(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the knowledge and correct practices of nurses concerning safe injection (SI) at Military Hospital 175 in 2024 and examine some associated factors. Subjects and Methods: A descriptive cross-sectional study was conducted on 395 nursing staff working in clinical departments of Military Hospital 175. Knowledge and practices were assessed through a self-administered questionnaire using Google Form. Results: The percentage of nurses with correct overall knowledge of SI was 80.76%, and the rate of correct practices was 79.24%. Analysis showed no statistically significant association between demographic characteristics, such as age group, gender, professional qualifications, years of service, and the correct knowledge and practices of nurses regarding SI. Conclusion: Enhancing nurses’ knowledge and practices regarding safe injection plays a crucial role in improving the quality of care and services, as well as increasing patient satisfaction.